The changing role of BIM-facilitated facilities management in the post-COVID era: A systematic literature review. Issue 3 (1st November 2022) - Ma, P; Chan, I Y S
Abstract: COVID-19 has become a long-term pandemic and pushed the re-interpretation of normality. Fighting against the pandemic and building a new normal in the post-COVID era requires constant and innovative approaches. Building information modeling (BIM) facilitated facilities management (FM) has been advocated as a powerful method to overcome the huge public health-related challenges. However, studies investigating the role of BIM-facilitated FM in the pandemic era are fragmented, and holistic knowledge is limited. Research objectives of this study are twofold: (1) to identify varying FM requirements after the outbreak of COVID-19, (2) to investigate how BIM-facilitated FM copes with changing requests in the pandemic period. To achieve the objectives, a systematic literature review was conducted. Currently, FM tends to be public health-centric, and highly emphasized requirements encompass the flexibility of space transformation for emergency purpose, effective and sufficient ventilation, reliable biosecurity, and strict anti-infection management. Based on centralized database and visualized model, BIM-facilitated FM enables space optimization, simulation and prediction of infection risk, monitoring and managing equipment operation, and effective information management, which enhances both hard and soft FM. This paper sheds light on the applications and directions of future BIM-facilitated FM research in protecting public health in the post-COVID era.